Sulfide solid electrolyte and preparation method and application thereof
A sulfide solid electrolyte with specific molecular composition and preparation method addresses stability issues, forming a dielectric layer to enhance lithium-ion battery performance and safety.
Patent Information
- Application Number
- CN202411545096.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-03
AI Technical Summary
Existing sulfide electrolytes suffer from poor chemical stability, reactivity with electrode materials, and susceptibility to air degradation, limiting their application in lithium-ion batteries due to irreversible capacity loss and safety hazards.
A sulfide solid electrolyte with a molecular formula Li f P 1-g E g S w O g Q z, where E is selected from Mg, Ca, Sr, Ba, Zn, Cr, or Pb, and Q is Cl, Br, or I, is prepared by mixing sources and calcining to form a dielectric layer at the electrolyte/lithium metal interface, enhancing air and chemical stability.
The solution improves the conductivity, air stability, and electrolyte/active material interface properties, preventing lithium dendrite formation, thereby enhancing the lifespan and safety of all-solid-state lithium-ion batteries.
Smart Images

Figure CN119253040A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium - ion batteries, and particularly to a sulfide solid electrolyte, a preparation method thereof, and an application thereof. Background Art
[0002] As the current mainstream secondary battery, lithium - ion batteries are widely used in fields such as electric vehicles and electronic products. However, the traditional lithium - ion batteries use flammable organic liquid electrolytes, which have safety hazards such as electrolyte leakage and flammability, restricting their further development. To overcome the safety problems of organic liquid electrolytes, solid electrolytes have become the key research direction for the next - generation battery technology.
[0003] Currently, most of the existing sulfide electrolytes have poor chemical stability. Sulfides are prone to side reactions with electrode materials, resulting in irreversible capacity loss and seriously affecting the cycle performance of the battery. In addition, sulfides are also prone to react with components in the air such as water and oxygen, leading to the deterioration of the electrolyte performance, etc. These problems severely limit the popularization of sulfide solid electrolytes in practical applications. Summary of the Invention
[0004] The present invention provides a sulfide solid electrolyte, a preparation method thereof, and an application thereof. By the sulfide solid electrolyte, the preparation method and the application provided by the present invention, it is possible to improve the conductivity stability of the sulfide solid electrolyte, enhance the air stability, and improve the electrolyte / active material interface properties, thereby improving the lifespan and safety of all - solid - state lithium - ion batteries and lithium batteries.
[0005] To solve the above - mentioned technical problems, the present invention provides a sulfide solid electrolyte, and the molecular formula of the sulfide solid electrolyte is Li f P 1-g E g S w O g Q z ; wherein, 5 < f < 10; 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2; E is selected from one or more of Mg, Ca, Sr, Ba, Zn, Cr, Sn, or Pb; Q is selected from one or more of Cl, Br, or I.
[0006] In an embodiment of the present invention, E is selected from Mg and Q is selected from Cl.
[0007] In an embodiment of the present invention, the value range of g is 0.01 ≤ g ≤ 0.1.
[0008] The present invention also provides a preparation method of the above - mentioned sulfide solid electrolyte, comprising the steps:
[0009] According to the chemical formula of the sulfide solid electrolyte, a Li source, a P source, an E source, a S source and a Q source are mixed in a stoichiometric amount, and the mixture is placed in a ball mill for ball milling to obtain a sulfide solid electrolyte precursor powder; and
[0010] The sulfide solid electrolyte precursor powder is calcined at a preset temperature to obtain the sulfide solid electrolyte.
[0011] In one embodiment of the present invention, the Li source is selected from one or more of LiCl, LiBr, LiI or Li2S; the P source is selected from one or more of elemental P, P2S5, P4S6, PCl5 or PBr5; the E source is selected from one or more of oxides of E or sulfides of E; the S source is selected from one or more of elemental S, Li2S, P2S5, P4S6, MgS, CaS, SrS, BaS, ZnS, CrS, SnS or PbS; the Q source is selected from one or more of LiCl, PCl5, LiBr, PBr5, LiI or I2; the O element in the chemical formula comes from the oxide of E.
[0012] In one embodiment of the present invention, the ball milling time is 1 hour to 48 hours, the ball milling speed is 50 rpm to 1500 rpm, and the ball-to-material ratio is 1:1 to 100:1.
[0013] In one embodiment of the present invention, the preset temperature is 400° C. to 600° C., and the calcination treatment time is 1 hour to 18 hours.
[0014] The present invention also provides an all-solid-state lithium-ion battery, comprising at least:
[0015] A positive electrode sheet, wherein the positive electrode sheet comprises a halide solid electrolyte, wherein the halide solid electrolyte comprises Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 ;
[0016] A negative electrode; and
[0017] A solid electrolyte membrane, wherein the solid electrolyte membrane is disposed between the adjacent positive electrode sheet and the negative electrode sheet, and the solid electrolyte membrane comprises the above-mentioned sulfide solid electrolyte.
[0018] In one embodiment of the present invention, the positive electrode plate includes a positive electrode active material, and the positive electrode active material is selected from one or more of lithium nickel cobalt manganese oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium cobalt oxide or lithium nickel cobalt aluminum oxide.
[0019] The present invention also provides an electronic device, comprising the all-solid-state lithium-ion battery described above.
[0020] In summary, the present invention proposes a sulfide solid electrolyte and its preparation method and application. By introducing E element, O element and Q element into the sulfide solid electrolyte, the air stability of the sulfide solid electrolyte is effectively improved, the H2S gas produced by atmospheric degradation is reduced, and the air stability and chemical stability of the sulfide solid electrolyte are enhanced. A special dielectric layer can be formed at the electrolyte / lithium metal negative electrode interface, which can ensure the ionic conductivity of the sulfide solid electrolyte, promote the rapid movement of lithium ions and the uniform distribution of the electric field. It can help control the nucleation and growth of lithium, prevent the formation of lithium dendrites, and can significantly improve the stability and performance of lithium-ion batteries, improve the life and safety of all-solid-state lithium-ion batteries. It can improve the stability of the conductivity of the sulfide solid electrolyte, enhance air stability, and improve the electrolyte / active material interface properties, thereby improving the compatibility with active materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0022] Figure 1 This is a 1C / 1C long cycle performance diagram of the all-solid-state lithium-ion battery in Example 3 at room temperature.
[0023] Figure 2 This is the SEM image of the sulfide solid electrolyte in Example 3. DETAILED DESCRIPTION
[0024] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0025] It should be understood that the present invention can be implemented in different forms and should not be interpreted as limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.
[0026] The technical solutions of the present invention will be further described in detail below in conjunction with several embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts fall within the scope of protection of the present invention.
[0027] The present invention provides a sulfide solid electrolyte, and the molecular formula of the sulfide solid electrolyte is Li f P 1- g E g S w O g Q z ; wherein, 5 < f < 10; 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2, E is selected from one or more of Mg, Ca, Sr, Ba, Zn, Cr, Sn or Pb, and Q is selected from one or more of Cl, Br or I. Among them, introducing E element and O element into the sulfide solid electrolyte rich in halogen elements will form P-O and E-S bonds in the crystal structure, effectively improving the air stability of the sulfide solid electrolyte, reducing the H2S gas generated by atmospheric degradation, and enhancing the air stability and chemical stability of the sulfide solid electrolyte. In addition, when using this sulfide solid electrolyte to assemble a all-solid-state lithium-ion battery, a special dielectric layer can be formed at the electrolyte / lithium metal anode interface. This dielectric layer contains components such as LiCl, Li2O and Li-Mg alloy. Among them, Li2O has good ionic conductivity, while Li-Mg alloy promotes the rapid movement of lithium ions and the uniform distribution of the electric field. The high interfacial energy of LiCl helps to control the nucleation and growth of lithium, preventing the formation of lithium dendrites. These characteristics combined effectively promote the diffusion of lithium ions between the electrodes and inhibit the growth of lithium dendrites. Therefore, the sulfide solid electrolyte provided by this application can significantly improve the stability and performance of lithium-ion batteries, and improve the lifespan and safety of all-solid-state lithium-ion batteries and lithium batteries.
[0028] In an embodiment of the present invention, E is, for example, selected from Mg. Doping with Mg can trigger the electron aggregation around the S atom, inhibit the electron acceptance of Li, and at the same time the generated self-limiting interface hinders the redox reaction between the sulfide electrolyte and Li metal. That is, by doping with Mg, the electron distribution in the sulfide solid electrolyte can be adjusted, the electron acceptance of Li can be inhibited, thereby reducing the parasitic redox reaction between the electrolyte and metallic lithium, improving the cycle stability and performance of the battery, and improving the practicality and reliability of the sulfide electrolyte.
[0029] In one embodiment of the present invention, Q selects a halogen element, and depending on the halogen, the degree of anion disorder between the 4a and 4c sites in the crystal structure of the sulfide solid electrolyte is different, ranging from a small amount of anti-site defects when Q is I to 60% site disorder when Q is Cl, and the lithium conductivity of these compounds mainly depends on the degree of disorder occupied by the anion and cation sites. Therefore, Q is selected as Cl, for example, to improve the ionic conductivity and electrochemical stability of the sulfide solid electrolyte and improve the voltage stability. The value range of g is 0.01≤g≤0.1. When the doping amount is too low, an effective dielectric layer may not be formed. Excessive doping will cause excessive lattice distortion and destroy the original crystal structure, which may lead to a decrease in the structural stability of the material, and even phase separation or amorphization, thereby reducing the ionic conductivity of the material. In a specific embodiment of the present invention, g is optimally 0.02 to improve the cycle performance of lithium-ion batteries.
[0030] The present invention also proposes a method for preparing a sulfide solid electrolyte, which at least comprises: according to the chemical formula of the sulfide solid electrolyte, a Li source, a P source, an E source, a S source and a Q source are mixed evenly according to a stoichiometric amount, and then placed in a ball mill for ball milling to obtain a sulfide solid electrolyte precursor powder; and the sulfide solid electrolyte precursor powder is calcined at a preset temperature to obtain a sulfide solid electrolyte.
[0031] In one embodiment of the present invention, according to the chemical formula of the sulfide solid electrolyte Li f P 1-g E g S w O g Q z , the Li source, P source, E source, S source and Q source are uniformly mixed according to stoichiometric ratio, wherein the Li source is selected from one or more of LiCl, LiBr, LiI or Li2S, the P source is selected from one or more of elemental P, P2S5, P4S6, PCl5 or PBr5, the E source is selected from one or more of oxides of E or sulfides of E, the S source is selected from one or more of elemental S, Li2S, P2S5, P4S6, MgS, CaS, SrS, BaS, ZnS, CrS, SnS or PbS, the Q source is selected from one or more of LiCl, PCl5, LiBr, PBr5, LiI or I2, and the O element in the chemical formula comes from the oxide of E. After the raw materials are evenly mixed, they are placed in a ball mill and ball milled in an inert gas atmosphere, wherein the ball-to-material ratio is, for example, 1:1 to 100:1, the ball milling speed is, for example, 50 rpm to 1500 rpm, and the ball milling time is, for example, 1 h to 48 h, to obtain a sulfide solid electrolyte precursor powder.
[0032] In one embodiment of the present invention, the sulfide solid electrolyte precursor powder is calcined at a preset temperature, wherein the preset temperature is 400° C. to 600° C., and the calcination time is 1 h to 18 h, to obtain a sulfide solid electrolyte.
[0033] The present invention also proposes an all-solid-state lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and a solid electrolyte membrane, wherein the solid electrolyte membrane is arranged between adjacent positive electrode sheets and negative electrode sheets. The positive electrode sheet comprises a positive electrode active material and a halide solid electrolyte, wherein the positive electrode active material is selected from one or more of lithium nickel cobalt manganese oxide (NCM), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium cobalt oxide (LCO) or lithium nickel cobalt aluminum oxide (NCA). The halide solid electrolyte comprises Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 , the halide solid electrolyte does not produce exothermic reaction with the de-lithium positive electrode active material, thereby improving the safety of the lithium-ion battery. The negative electrode plate is, for example, one or more of a metal lithium plate, a metal indium plate, or a lithium-indium alloy plate, and the negative electrode plate includes, for example, a negative electrode active material, and the negative electrode active material is selected from one or more of a graphite material, a silicon material, or a composite material of a graphite material and a silicon material. The solid electrolyte membrane includes the above-mentioned sulfide solid electrolyte to improve the performance of the all-solid-state lithium-ion battery.
[0034] In one embodiment of the present invention, the positive electrode plate further includes a conductive agent and a binder, wherein the conductive agent is, for example, one or a combination of at least two of conductive carbon black (Super P, SP), carbon nanotubes (Carbon Nano-tube, CNT), vapor grown carbon fiber (Vapor Grown Carbon Fiber, VGCF) or graphene. The binder is, for example, polytetrafluoroethylene (PTFE) and its derivatives. The mass ratio of the positive electrode active material, the halide solid electrolyte, the conductive agent and the binder is, for example, (65-78): (20-30): (1-3): (1-2). In this embodiment, the mass ratio of the positive electrode active material, the halide solid electrolyte, the conductive agent and the binder is, for example, 69:29:1:1, and the conductive agent is a combination of conductive carbon black (super-P) and vapor grown carbon fiber (VGCF), and the mass ratio of the conductive carbon black and the vapor grown carbon fiber is 1:1, and the binder is, for example, polytetrafluoroethylene. After the positive electrode active material, the halide solid electrolyte, the conductive agent and the binder are uniformly mixed, a mixed powder is obtained, and the positive electrode plate is obtained by dry pressing. In one embodiment of the present invention, when the negative electrode plate includes the negative electrode active material, the negative electrode plate also includes a solid electrolyte, a conductive agent and a binder, etc., wherein the solid electrolyte is, for example, a halide solid electrolyte or a sulfide electrolyte, etc., and this application does not make specific restrictions. The binder is, for example, at least one of polyisoprene, polyethylene or polypropylene, and the conductive agent is, for example, at least one of carbon nanotubes, carbon fibers or acetylene black. This application does not limit the ratio of the negative electrode active material, the solid electrolyte, the conductive agent and the binder, and the selection is made according to the manufacturing requirements, and the negative electrode plate is obtained, for example, by dry pressing.
[0035] In one embodiment of the present invention, in order to obtain the performance of a sulfide solid electrolyte, for example, the sulfide solid electrolyte is cold pressed under a preset pressure to obtain a solid electrolyte membrane, wherein the preset pressure is, for example, 300MPa to 400MPa, and the thickness of the solid electrolyte membrane is, for example, 100μm to 500μm.
[0036] In one embodiment of the present invention, the negative electrode sheet is, for example, a metal lithium sheet, and the positive electrode sheet, the solid electrolyte membrane sheet, and the negative electrode sheet are placed in sequence, pressurized, and sealed in a vacuum or inert atmosphere to obtain an all-solid-state lithium-ion battery. The assembly process of the all-solid-state lithium-ion battery is, for example, completed in a glove box with an argon atmosphere.
[0037] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.
[0038] Example 1
[0039] Preparation of sulfide solid electrolyte: In an argon atmosphere, 2.015 mol of Li2S, 1.5 mol of LiCl, 0.495 mol of P2S5 and 0.01 mol of MgO were placed in a tungsten steel ball mill, and tungsten steel balls were added at a ball-to-material ratio of 40:1. The ball mill was milled at 100 rpm for 10 minutes, and then at 500 rpm for 16 hours to obtain a uniformly mixed sulfide solid electrolyte precursor powder. The sulfide solid electrolyte precursor powder was placed in a crucible, sintered at 500 ° C for 10 hours, and Li was obtained after cooling. 5.5 3P 0.99 Mg 0.01 S 4.49 O 0.01 Cl 1.5 .
[0040] Preparation of electrolyte membrane: 50 mg of Li 5.5 P 0.99 Sb 0.01 S 4.475 O 0.025 Cl 1.5 The electrolyte membrane was prepared by cold pressing at 360 MPa, and the electrolyte membrane had a thickness of 400 μm and a diameter of 10 mm.
[0041] Preparation of positive electrode: LiNi 0.8 Co 0.1 Mn 0.1 O2, conductive agent, Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 The PTFE preparation is mixed in a mass ratio of 69:1:29:1, and the positive electrode sheet is made by a dry method. The conductive agent is super-P and VGCF in a mass ratio of 1:1, and then the positive electrode sheet is cut into discs with a diameter of 10 mm.
[0042] Negative electrode sheet: The negative electrode sheet is made of lithium metal sheet and cut into round sheets with a diameter of 10 mm.
[0043] Assembly of all-solid-state battery: Assemble the positive electrode sheet, electrolyte membrane sheet and negative electrode sheet prepared above into an all-solid-state battery.
[0044] Assembly of symmetrical battery: Place the counter electrode Li on both sides of the electrolyte membrane and assemble it with the electrolyte membrane into a Li / Li symmetrical battery.
[0045] Example 2
[0046] The chemical formula of the sulfide solid electrolyte prepared by 2.0225 mol Li2S, 1.5 mol LiCl, 0.4925 mol P2S5 and 0.015 mol MgO is Li 5.545 P 0.985 Mg 0.015 S 4.485 O 0.015 Cl 1.5 , other operations remain the same as those in Example 1.
[0047] Example 3
[0048] The chemical formula of the sulfide solid electrolyte prepared by 2.03 mol Li2S, 1.5 mol LiCl, 0.49 mol P2S5 and 0.02 mol MgO is Li 5.56 P 0.98 Mg 0.02 S 4.48 O 0.02 Cl 1.5 , other operations remain the same as those in Example 1.
[0049] Example 4
[0050] The chemical formula of the sulfide solid electrolyte prepared by 2.06 mol Li2S, 1.5 mol LiCl, 0.48 mol P2S5 and 0.04 mol MgO is Li 5.62 P 0.96 Mg 0.04 S 4.46 O 0.04 Cl 1.5 , other operations remain the same as those in Example 1.
[0051] Example 5
[0052] The sulfide solid electrolyte prepared by 2.09 mol Li2S, 1.5 mol LiCl, 0.47 mol P2S5 and 0.06 mol MgO is Li 5.68 P 0.94 Mg 0.06 S 4.44 O 0.06 Cl 1.5 , other operations remain the same as those in Example 1.
[0053] Example 6
[0054] The chemical formula of the sulfide solid electrolyte prepared by 2.12 mol Li2S, 1.5 mol LiCl, 0.46 mol P2S5 and 0.08 mol MgO is Li 5.74 P 0.92 Mg0.08 S 4.42 O 0.02 Cl 1.5 , other operations remain the same as those in Example 1.
[0055] Example 7
[0056] The chemical formula of the sulfide solid electrolyte prepared by 2.15 mol Li2S, 1.5 mol LiCl, 0.45 mol P2S5 and 0.1 mol MgO is Li 5.8 P 0.9 Mg 0.1 S 4.48 O 0.1 Cl 1.5 , other operations remain the same as those in Example 1.
[0057] Example 8
[0058] The chemical formula of the sulfide solid electrolyte prepared by 1.83 mol Li2S, 1.9 mol LiCl, 0.49 mol P2S5 and 0.02 mol MgO is Li 5.16 P 0.98 Mg 0.02 S 4.08 O 0.02 Cl 1.9 , other operations remain the same as those in Example 1.
[0059] Example 9
[0060] The chemical formula of the sulfide solid electrolyte prepared by 2.53 mol Li2S, 1 mol LiCl, 0.49 mol P2S5 and 0.02 mol MgO is Li 6.06 P 0.98 Mg 0.02 S 4.98 O 0.02 C1, other operations are consistent with those in Example 1.
[0061] Example 10
[0062] The chemical formula of the sulfide solid electrolyte prepared by 3.03 mol Li2S, 0.5 mol LiCl, 0.49 mol P2S5 and 0.02 mol MgO is Li 6.56 P 0.98 Mg 0.02 S 5.48 O 0.02 Cl 0.5 , other operations remain the same as those in Example 1.
[0063] Embodiment 11
[0064] The chemical formula of the sulfide solid electrolyte prepared by 3.43 mol Li2S, 0.1 mol LiCl, 0.49 mol P2S5 and 0.02 mol MgO is Li 6.96 P 0.98 Mg 0.02 S 5.88 O 0.02 Cl 0.1 , other operations remain the same as those in Example 1.
[0065] Example 12
[0066] The chemical formula of the sulfide solid electrolyte prepared by 2.03 mol Li2S, 1.4 mol LiCl, 0.1 mol LiBr, 0.49 mol P2S5 and 0.02 mol MgO is Li 5.56 P 0.98 Mg 0.02 S 4.48 O 0.02 Cl 1.4 Br 0.1 , other operations remain the same as those in Example 1.
[0067] Embodiment 13
[0068] The chemical formula of the sulfide solid electrolyte prepared by 2.03 mol Li2S, 0.1 mol LiCl, 1.4 mol LiBr, 0.49 mol P2S5 and 0.02 mol MgO is Li 5.56 P 0.98 Mg 0.02 S 4.48 O 0.02 Cl 0.1 Br 1.4 , other operations remain the same as those in Example 1.
[0069] Embodiment 14
[0070] The chemical formula of the sulfide solid electrolyte prepared by 2.03 mol Li2S, 1.3 mol LiCl, 0.1 mol LiBr, 0.1 mol LiI, 0.49 mol P2S5 and 0.02 mol MgO is Li 5.56 P 0.98 Mg 0.02 S 4.48 O 0.02 Cl 1.3 Br 0.1 I0 .1 , other operations remain the same as those in Example 1.
[0071] Embodiment 15
[0072] The chemical formula of the sulfide solid electrolyte prepared by 2.03 mol Li2S, 0.1 mol LiCl, 1.3 mol LiBr, 0.1 mol LiI, 0.49 mol P2S5 and 0.02 mol MgO is Li 5.56 P 0.98 Mg 0.02 S 4.48 O 0.02 Cl 0.1 Br 1.3 I0 .1 , other operations remain the same as those in Example 1.
[0073] Example 16
[0074] The chemical formula of the sulfide solid electrolyte prepared by 2.03 mol Li2S, 1.5 mol LiCl, 0.49 mol P2S5 and 0.02 mol CaO is Li 5.56 P 0.98 Ca 0.02 S 4.48 O 0.02 Cl 1.5 , other operations remain the same as those in Example 1.
[0075] Embodiment 17
[0076] The chemical formula of the sulfide solid electrolyte prepared by 2.03 mol Li2S, 1.5 mol LiCl, 0.49 mol P2S5 and 0.02 mol ZnO is Li 5.56 P 0.98 Zn 0.02 S 4.48 O 0.02 Cl 1.5 , other operations remain the same as those in Example 1.
[0077] Comparative Example 1
[0078] The chemical formula of the sulfide solid electrolyte prepared by 2 mol of Li2S, 1.5 mol of LiCl and 0.5 mol of P2S5 is Li 5.5 PS 4.5 Cl 1.5 , other operations remain the same as those in Example 1.
[0079] Comparative Example 2
[0080] The chemical formula of the sulfide solid electrolyte prepared by 2 mol of Li2S, 1.4 mol of LiCl, 0.1 mol of LiBr and 0.5 mol of P2S5 is Li 5.5 PS4.5 Cl 1.4 Br 0.1 , other operations remain the same as those in Example 1.
[0081] Comparative Example 3
[0082] The electrolyte chemical formula is Li prepared by 2 mol Li2S, 1.3 mol LiCl, 0.1 mol LiBr, 0.1 mol LiI and 0.5 mol P2S5. 5.5 PS 4.5 Cl 1.3 Br 0.1 I 0.1 , other operations remain the same as those in Example 1.
[0083] In Examples 1-17 and Comparative Examples 1-3 of the present invention, different sulfide solid electrolytes are used to test the ionic conductivity of the sulfide solid electrolytes, and the sulfide solid electrolytes are exposed to a dry room at -40°C for 24 hours, and then the ionic conductivity test is performed again. In this embodiment, the ionic conductivity is obtained, for example, by an AC impedance method, and the test results are shown in Table 1.
[0084] In Examples 1-17 and Comparative Examples 1-3 of the present invention, different sulfide solid electrolytes are used to obtain lithium-ion batteries. The lithium-ion batteries prepared above are subjected to long-cycle charge and discharge at 25°C, and their discharge capacity is measured, and the energy density is calculated. The working voltage range of the battery test is 2.5V to 4.3V, the charge and discharge rate is 1C / 1C, and the discharge capacity of the first cycle is recorded as the 1C discharge capacity. When the battery capacity reaches 80% of the first cycle capacity (80% State of Health, 80% SOH), the test is terminated to obtain the number of cycles at room temperature. The symmetrical battery is charged at 1 mA / cm 2 The constant current charge-discharge cycle test was carried out at a current density of , and the test results are shown in Table 2.
[0085] Table 1. Ionic conductivity of sulfide solid electrolytes in Examples 1-17 and Comparative Examples 1-3
[0086]
[0087] Table 2. Test results of lithium-ion batteries and symmetrical batteries in Examples 1-17 and Comparative Examples 1-3
[0088]
[0089] As shown in Table 1 and Table 2, it can be seen from the comparison between Examples 1-17 and Comparison 1-3 that when the E element and the O element are not added to the electrolyte, the lithium-ion battery has almost no cycle performance and a short circuit occurs quickly, indicating that when the E element and the O element are missing, the chemical stability of the sulfide solid electrolyte material is poor, the mechanical strength is insufficient, and it is difficult to ensure the long-term cycle performance of the lithium-ion battery. By introducing the E element and the O element, the cycle performance of the lithium-ion battery can be improved.
[0090] Please refer to Table 1 and Table 2. It can be seen from 1-7 in the comparative examples that when the E element in the sulfide solid electrolyte selects Mg, as the doping amount of Mg increases, the cycle performance of the lithium ion battery gradually increases and then gradually decreases. And as the doping amount of the E element increases, the ionic conductivity of the sulfide solid electrolyte decreases, but the ionic conductivity retention rate after exposure to -40°C dry room for 24h increases, enhancing the air stability and chemical stability of the sulfide solid electrolyte, and improving the stability and performance of the battery. Therefore, controlling the doping amount of E in the sulfide solid electrolyte can improve the cycle life and safety of the all-solid-state lithium ion battery, while maintaining the ionic conductivity and ionic conductivity retention rate at a high level, ensuring the rate performance of the lithium ion battery, and improving the charge and discharge efficiency and cycle life. High ionic conductivity can reduce the internal resistance of the battery and improve the power density and energy density of the battery.
[0091] See also Figure 1 As shown, in the all-solid-state lithium-ion battery of Example 3, during the cycle at room temperature, the current density used for constant current charging and discharging is 1C, Figure 1 It can be seen that at a current density of 1C, the all-solid-state lithium-ion battery in Example 3 still has an energy storage capacity of about 150 mAh / g after 500 cycles, indicating that the sulfide solid electrolyte has excellent reaction kinetics and cycle stability, and the obtained solid electrolyte membrane has a good gain effect on the cycle stability and reaction activity specific capacity of the battery. The all-solid-state lithium-ion battery has excellent specific capacity, rate performance and cycle life.
[0092] See also Figure 2 As shown, the sulfide solid electrolyte obtained in Example 3 was characterized by scanning electron microscope (SEM) images. Figure 2 It can be seen that the sulfide solid electrolyte has a regular shape, clear boundaries, a compact structure, and fewer pores, which can be beneficial to maintaining the ionic conductivity of the sulfide solid electrolyte, thereby improving the retention rate of ionic conductivity.
[0093] As shown in Table 1 and Table 2, by comparing Examples 3, 8-11, it can be seen that when the Mg doping amount in the sulfide solid electrolyte is the same, increasing or decreasing the Cl element content will cause a serious decrease in ionic conductivity and reduce the cycle performance of the lithium-ion battery. Therefore, the Cl element content is controlled to ensure the ionic conductivity of the sulfide solid electrolyte and the performance of the lithium-ion battery.
[0094] Please refer to Table 1 and Table 2. Comparison Examples 3, 12-15 show that when the Mg doping amount in the sulfide solid electrolyte is the same, the addition of one or more of the Br or I elements will reduce the battery's cycle performance. Therefore, Q selects the Cl element, which can improve the ionic conductivity and electrochemical stability of the sulfide solid electrolyte and improve the voltage stability. Comparison Examples 3, 16-17 show that when the E doping element selects other elements, it can also increase the ionic conductivity retention rate, improve the stability of the sulfide solid electrolyte, and improve the cycle performance of the lithium-ion battery, but it is weaker than Mg doping. Therefore, when Mg is doped, the performance of the lithium-ion battery is best.
[0095] The present invention also provides an electronic device, the electronic device includes at least one of the above-mentioned lithium-ion batteries, and the lithium-ion battery is used to provide electrical energy. Among them, the electronic device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy and an electric tool, etc. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. Spacecraft include airplanes, rockets, space shuttles and spacecrafts, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. The electronic device includes the above-mentioned lithium-ion battery, so the advantages of the above-mentioned lithium-ion battery are included, which will not be elaborated here.
[0096] In summary, the present invention proposes a sulfide solid electrolyte and its preparation method and application. By introducing E element, O element and Q element into the sulfide solid electrolyte, the air stability of the sulfide solid electrolyte is effectively improved, the H2S gas produced by atmospheric degradation is reduced, and the air stability and chemical stability of the sulfide solid electrolyte are enhanced. A special dielectric layer can be formed at the electrolyte / lithium metal negative electrode interface, which can ensure the ionic conductivity of the sulfide solid electrolyte, promote the rapid movement of lithium ions and the uniform distribution of the electric field. It can help control the nucleation and growth of lithium, prevent the formation of lithium dendrites, and significantly improve the stability and performance of lithium-ion batteries, improve the life and safety of all-solid-state lithium-ion batteries. It can improve the stability of the conductivity of the sulfide solid electrolyte, enhance air stability and improve the electrolyte / active material interface properties, thereby improving compatibility with active materials.
[0097] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.
[0098] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.
Claims
1. A sulfide solid electrolyte, characterized in that: The molecular formula of the sulfide solid electrolyte is Li f P 1- g E g S w O g Q z ; where 5 < f < 10; 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2; E is selected from one or more of Mg, Ca, Sr, Ba, Zn, Cr, Sn or Pb; Q is selected from one or more of Cl, Br or I.
2. The sulfide solid electrolyte according to claim 1, characterized in that E is selected from Mg, and Q is selected from Cl.
3. The sulfide solid electrolyte according to claim 1, characterized in that The value range of g is 0.01≤g≤0.
1.
4. A method for preparing a sulfide solid electrolyte according to any one of claims 1 to 3, characterized in that: Includes steps: According to the chemical formula of the sulfide solid electrolyte, a Li source, a P source, an E source, a S source and a Q source are mixed in a stoichiometric amount, and the mixture is placed in a ball mill for ball milling to obtain a sulfide solid electrolyte precursor powder; and The sulfide solid electrolyte precursor powder is calcined at a preset temperature to obtain the sulfide solid electrolyte.
5. The method for preparing a sulfide solid electrolyte according to claim 4, characterized in that: The Li source is selected from one or more of LiCl, LiBr, LiI or Li2S; the P source is selected from one or more of elemental P, P2S5, P4S6, PCl5 or PBr5; the E source is selected from one or more of E oxides or E sulfides; the S source is selected from one or more of elemental S, Li2S, P2S5, P4S6, MgS, CaS, SrS, BaS, ZnS, CrS, SnS or PbS; the Q source is selected from one or more of LiCl, PCl5, LiBr, PBr5, LiI or I2; the O element in the chemical formula comes from the oxide of E.
6. The method for preparing a sulfide solid electrolyte according to claim 4, characterized in that: The ball milling time is 1h to 48h, the ball milling speed is 50rpm to 1500rpm, and the ball-to-material ratio is 1:1 to 100:
1.
7. The method for preparing a sulfide solid electrolyte according to claim 4, characterized in that: The preset temperature is 400° C. to 600° C., and the calcination treatment time is 1 hour to 18 hours.
8. An all-solid-state lithium-ion battery, characterized in that: At least: A positive electrode sheet, wherein the positive electrode sheet comprises a halide solid electrolyte, wherein the halide solid electrolyte comprises Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 ; A negative electrode; and A solid electrolyte membrane, wherein the solid electrolyte membrane is disposed between the adjacent positive electrode sheet and the negative electrode sheet, and the solid electrolyte membrane comprises the sulfide solid electrolyte according to any one of claims 1 to 3.
9. The all-solid-state lithium-ion battery according to claim 8, characterized in that: The positive electrode plate includes a positive electrode active material, and the positive electrode active material is selected from one or more of lithium nickel cobalt manganese oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium cobalt oxide or lithium nickel cobalt aluminum oxide.
10. An electronic device, characterized in that: An all-solid-state lithium-ion battery comprising any one of claims 8 to 9.
Citation Information
Cited By
Sulfide solid electrolyte and preparation method and application thereof
EP4796495A1